Two loss‐of‐function ANKRD11 variants in Chinese patients with short stature and a possible molecular pathway. Issue 3 (22nd December 2020) - Zhang, Tingting; Yang, Yun; Yin, Xueling; Wang, Xueqing; Ni, Jihong; Dong, Zhiya; Li, Chuanyin; Lu, Wenli
Abstract: KBG syndrome is a rare genetic disease characterized mainly by skeletal abnormalities, distinctive facial features, and intellectual disability. Heterozygous mutations in ANKRD11 gene, or deletion of 16q24.3 that includes ANKRD11 gene are the cause of KBG syndrome. We describe two patients presenting with short stature and partial facial features, whereas no intellectual disability or hearing loss was observed in them. Two ANKRD11 variants, c.4039_4041del (p. Lys1347del) and c.6427C > G (p. Leu2143Val), were identified in this study. Both of them were classified as variants of uncertain significance (VOUS) by ACMG/AMP guidelines and were inherited from their mothers. ANKRD11 could enhance the transactivation of p21 gene, which was identified to participate in chondrogenic differentiation. In this study, we demonstrated that the knockdown of ANKRD11 could reduce the p21 ‐promoter luciferase activities while re‐introduction of wild type ANKRD11, but not ANKRD11 variants (p. Lys1347del or p. Leu2143Val), could restore the p21 levels. Thus, our study report two loss‐of‐function ANKRD11 variants which might provide new insight on pathogenic mechanism that correlates ANKRD11 variants with the short stature phenotype of KBG syndrome.